1993
DOI: 10.1523/jneurosci.13-09-03878.1993
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenaline hyperpolarizes identified rat mesopontine cholinergic neurons in vitro

Abstract: Inhibition of brainstem cholinergic neurons by noradrenergic neurons of the locus ceruleus has long been suggested as a key mechanism of behavioral state control. In particular, the commonly held view is that noradrenaline (NA) plays a permissive role in rapid eye movement (REM) sleep generation by disinhibiting brainstem cholinergic neurons. While this notion has been supported by numerous investigations, the inhibition of cholinergic neurons by NA has never been directly demonstrated. The purpose of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
1
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 41 publications
6
60
1
1
Order By: Relevance
“…The average reversal potential for the NE-induced conductance was consistent with a K ϩ conductance, although reversal potentials for some cells also suggested a role for a Cl Ϫ conductance. Similar ␣2-adrenergic receptor-mediated increases in K ϩ conductance are found in several brain areas, including locus coeruleus (Aghajanian and VanderMaelen 1982;Egan et al 1983), brain stem cholinergic neurons (Williams and Reiner 1993), hypothalamus (Li and van den Pol 2005), septum (Liu and Alreja 1998), and cerebral cortex (Blanton and Kriegstein 1992). Thus the action of NE described here on avian forebrain neurons is shared across diverse brain areas and taxa.…”
Section: Mechanisms Of Ne Actionsupporting
confidence: 76%
See 1 more Smart Citation
“…The average reversal potential for the NE-induced conductance was consistent with a K ϩ conductance, although reversal potentials for some cells also suggested a role for a Cl Ϫ conductance. Similar ␣2-adrenergic receptor-mediated increases in K ϩ conductance are found in several brain areas, including locus coeruleus (Aghajanian and VanderMaelen 1982;Egan et al 1983), brain stem cholinergic neurons (Williams and Reiner 1993), hypothalamus (Li and van den Pol 2005), septum (Liu and Alreja 1998), and cerebral cortex (Blanton and Kriegstein 1992). Thus the action of NE described here on avian forebrain neurons is shared across diverse brain areas and taxa.…”
Section: Mechanisms Of Ne Actionsupporting
confidence: 76%
“…This difference could be more pronounced in avian adrenergic receptors. Nevertheless, studies in other species have found a similar inability of clonidine to mimic fully ␣2-adrenergic receptormediated effects (Blanton and Kriegstein 1992;Liu and Alreja 1998;Williams and Reiner 1993), which may indicate the existence of a novel ␣2-adrenergic receptor subtype. A third possibility is that the action of clonidine on imidazoline receptors could interfere with the suppressive effect of ␣2-adrenergic receptor activation, although previous studies have found only a synergistic effect between these two receptor types (Georges and Aston-Jones 2003;Georges et al 2005).…”
Section: Mechanisms Of Ne Actionmentioning
confidence: 95%
“…The finding that the ␣ 2 -AR agonist UK14,304 and the ␣ 2 -AR antagonists atipamezole and RX821002, respectively, suppressed and enhanced frontocortical ACh release demonstrates that ␣ 2 -ARs exert a tonic, inhibitory influence upon ACh release in the FCX of conscious rats. This observation amplifies findings of in vitro studies (Williams and Reiner, 1993) and in vivo studies using AChE inhibitors (Moroni et al, 1983;Tellez et al, 1997). Furthermore, ACh release was reduced by the preferential ␣ 2A -AR agonist guanabenz and accelerated by the selective ␣ 2A -AR antagonist BRL44408 (Young et al, 1989;Renouard et al, 1994), suggesting a role for the ␣ 2A -AR subtype in this effect.…”
Section: Downloaded Fromsupporting
confidence: 64%
“…Nevertheless, bupropion did not affect REM sleep in our study, which is altered by NE reuptake inhibitors and DA agonists. In the rat, NE has been shown to directly inhibit the cholinergic cells of the dorsolateral mesopontine tegmentum (Williams and Reiner 1993). If bupropion enhances NE neurotransmission to the cholinergic neurons in the lateral dorsal mesopontine tegmentum, we might expect REM sleep to be decreased.…”
Section: Discussionmentioning
confidence: 99%